2008
DOI: 10.1007/bf02982707
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intervention in older adults with early-stage Alzheimer Dementia: Early lessons learned

Abstract: In older adults, an adequate diet depends on their ability to procure and prepare food and eat independently or the availability of dietary assistance when needed. Inadequate food intake or increased nutritional requirements lead to poor nutritional status, which is considered a key determinant of morbidity, increased risk of infection, and mortality in elderly individuals. Weight loss among seniors also heralds increased morbidity and mortality. Dietary behaviour disorders affecting food consumption, nutritio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 50 publications
0
40
0
Order By: Relevance
“…Most intervention research to date has emphasized eating behaviours and improving food intake and nutritional status of persons with dementia [14, 34, 35, 46]. When discussing mealtime activities and behaviours, a negative discourse is often used, focusing on decline [28] and using terms such as ‘aversive eating behaviors’ [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most intervention research to date has emphasized eating behaviours and improving food intake and nutritional status of persons with dementia [14, 34, 35, 46]. When discussing mealtime activities and behaviours, a negative discourse is often used, focusing on decline [28] and using terms such as ‘aversive eating behaviors’ [29].…”
Section: Discussionmentioning
confidence: 99%
“…Work to date suggests challenges in coping with the many changes experienced in mealtime activities leads to caregiver stress [9, 28, 29] and this stress predicts weight loss in the person with dementia [33]. Education delivered in family caregiver support programs tends to be focused on how to change diet, maintain body weight, and access external resources [14, 34, 35]. Based on the knowledge that mealtimes are more than ‘food on the plate’, an examination of strategies to support the mealtime process developed and used by families living with dementia is needed to provide a more comprehensive basis for these education programs.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, nutrient intakes from diet and supplements were higher in control subjects, with significant differences in energy, the macronutrients calcium, iron, zinc, vitamin K, vitamin A, and dietary fiber as well as n -3 and n -6 fatty acids [63]. The authors suggested that suboptimal diet is early in the onset of the disease and that AD patients would benefit from systematic dietary assessment and intervention to prevent further deterioration in food consumption and increased nutritional risk.…”
Section: Lifestyle-related Risk Factors For Dementia and Possible mentioning
confidence: 95%
“…Recently, the alteration of the feeding behavior in an AD model animal was reported for the first time (31,32). APP23 Tg mice overexpressing human APP cDNA encoding the Swedish double mutation (K670N/M671L) under the control of the neuron-specific murine Thy-1.2 promoter showed the pathological features, learning and memory deficits analogous to AD patients (33).…”
Section: Discussionmentioning
confidence: 99%